Understanding Moral Values in the Memoir Entitled Educated by Tara Westover - Pratiwi, Desak Putu Eka; Sri Rwa Jayantini, I Gusti Agung; Ade Pratama, I Putu (Lingual Journal of Language and Culture; Vol 15 No 1 (2023): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2023.v15.i01.p04, 2023)
This article is focused on how to analyse any moral values portrayed in the memoir "Educated," with particular emphasis on the protagonist, Tara Westover. The study intends to identify conflicts encountered by the main character through narration or dialogues with other characters, and to reveal moral values that emerge as she overcomes these conflicts. The research utilized a qualitative descriptive method and drew on the conflict theory proposed by Stanton (1965) and the theory of moral values put forth by Linda and Eyre (1993) to analyse data from the memoir. Two of the conflicts found in this study were both internal struggles by the main character involving her thoughts and feelings and external struggles with her father, abusive older brother, and family members who labelled her as a dangerous girl influenced by Satan. Through her resolution on these conflicts, the main character demonstrated various moral values, including self-reliance, self-discipline, courage, and respect. The study's findings emphasize the significance of spiritual metamorphosis in memoirs and literature, as well as how conflicts can facilitate such transformation. Keywords : conflicts, moral values, main character, memoir